Gender Dysphoria and Sexual Orientation in The Islamic Perspective: A Conceptual Review of Identity, Fitrah, and Therapeutic Implications - Muslimah Paxia Ilyas; M. Darwis Hude; Nurbaiti (MUWAZAH : jurnal kajian gender, 2025)
Gender dysphoria, as a condition of discomfort resulting from a mismatch between gender identity and biological sex, is analyzed as a complex biopsychosocial problem. Gender identity disorder is a psychological condition that is distinct from sexual orientation, but there is also a relationship. Although society generally interprets this disorder as only being experienced by   transgender people,  the fact is that people who are not transgender can also suffer from this disorder. This study uses a qualitative-analytical method through literature review and thematic analysis of the collected textual data. The result is a prohibition against physical changes made by individuals with gender dysphoria or otherwise, based on efforts to preserve the authenticity of creation (fitrah) and prevent harm. Exceptions are only made for intersex conditions that require biological clarification. As an alternative, the recommended treatment is through a psychological-spiritual approach. Given that gender dysphoria is closely related to psychological disorders resulting from such discomfort, psychotherapy such as cognitive behavioral therapy, individual, family, and group therapy is considered more in line with human nature. This approach aims to help individuals manage dysphoria, strengthen self-acceptance, and align their psychological condition with the nature of creation, rather than making physical changes that are prohibited.